Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/jia2.25165
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hypermethylated genes as markers for cervical screening in women living with HIV

Abstract: IntroductionTo evaluate the performance of hypermethylation analysis of ASCL1,LHX8 and ST6GALNAC5 in physician‐taken cervical scrapes for detection of cervical cancer and cervical intraepithelial neoplasia (CIN) grade 3 in women living with HIV (WLHIV) in South Africa.MethodsSamples from a prospective observational cohort study were used for these analyses. Two cohorts were included: a cohort of WLHIV who were invited for cervical screening (n = 321) and a gynaecologic outpatient cohort of women referred for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…ASCL1 and LHX8 correlated well with CIN3 + (AUC 0.79 and 0.81, respectively) and ST6GALNAC5 correlated moderately with CIN3 + (AUC 0.71) of ASCL1, LHX8, and ST6GALNAC5 exhibited 72.1, 73.8, and 55.7% sensitivity with CIN3 + , respectively. In conclusion, ASCL1 and LHX8 have better performance and higher sensitivity, thereby making them suitable biomarkers for early diagnosis (Kremer et al, 2018). Interestingly, ASCL1 functions as an oncogenic transcription factor in lung cancer (Lenhart et al, 2015).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 92%
See 4 more Smart Citations
“…ASCL1 and LHX8 correlated well with CIN3 + (AUC 0.79 and 0.81, respectively) and ST6GALNAC5 correlated moderately with CIN3 + (AUC 0.71) of ASCL1, LHX8, and ST6GALNAC5 exhibited 72.1, 73.8, and 55.7% sensitivity with CIN3 + , respectively. In conclusion, ASCL1 and LHX8 have better performance and higher sensitivity, thereby making them suitable biomarkers for early diagnosis (Kremer et al, 2018). Interestingly, ASCL1 functions as an oncogenic transcription factor in lung cancer (Lenhart et al, 2015).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 92%
“…Other reports have not been successful in correlating LHX8 to cancer. However, Kremer et al (2018) have reported increasing levels of hypermethylated ASCL1 and LHX8 with increasing severity of cervical cancer. This could be attributed to contamination by other factors like the human immunodeficiency virus (owing to the infected patient cohort).…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 96%
See 3 more Smart Citations